Virologic survey in stranded cetaceans from northern Portugal : insights on Cetacean poxvirus and Cetacean coronavirus - Jorge, Diana Vieira (Universidade de Lisboa, Faculdade de Medicina Veterinária, 2022)
Dissertação de Mestrado Integrado em Medicina Veterinária, área científica de Sanidade Animal With an extended coastline, Portuguese waters harbor different resident and migratory species. It also registers a substantial amount of strandings every year (approximately 236 per year), which, under the supervision of ICNF, enabled the creation of a Marine Animal Tissue Bank, where tissue samples are stored for posterior analysis. Cetacean poxvirus is responsible for poxvirus skin disease, (pinhole or ring-like lesions) and tattoo skin disease. Phylogenetically 6 species are now identified (CePV1-6). Although this virus is not connected with high mortality rates, it may be lethal to neonates and calves without maternal immunity, severely impairing small isolated populations. To evaluate Poxvirus genetic diversity in skin lesions macroscopically compatible with Poxvirus, 47 samples collected between 2011 and 2015, from 4 different species of dolphins (Delphinus delphis, Tursiops truncates, Phocoena phocoena and Stenella coeruleoalba) were analyzed using a conventional PCR with a set of degenerate primers, previously designed for cetacean poxvirus screening. The positive samples (n=28, 58.33%) were further tested for the DNA polymerase gene, yielding 19 (40.4%) positive samples. After direct sequencing, a phylogenetic tree was designed based on the amino acidic sequences allowing the discrimination of 3 genetic clusters, genetically closer with CePV-1, CePV-5, CePV-3 and CePV-6. An unassigned cluster was also identified, suggesting the presence of a seventh subgroup (CePV-7). Contrary to cetacean poxvirus, Cetacean coronavirus was recently identified and included in the Gammacoronavirus genera. Since its discovery in 2008, cetacean coronavirus was detected in Hong Kong and United States in captives or semi-captive bottlenose dolphins presenting anorexia, diarrhea and lethargy. The movement, dispersion, and incidence of this virus in the wild is still unknown. It is important to highlight the taxonomic assignment of ...